ANALISIS BERPIKIR LITERASI MATEMATIKA SISWA DALAM MENYELESAIKAN SOAL MATEMATIKA PADA POKOK BAHASAN POLA BILANGAN BERDASARKAN KECERDASAN MAJEMUK - Aini, Novi Rosidatul; Suharto, S; Yudianto, Erfan; Trapsilasiwi, Dinawati; Setiawan, Toto Bara (Kadikma, 2018)
Abstract This reseach was conducted to describe students mathematical literacy in solving mathematical questions on the subject of number patterns based on multiple intelligences. The instruments used were questionnaires, math tests, and interviews. The research subjects were six students consisting of two students with verbal linguistic intelligence, two students with mathematical logical intelligence and two students with naturalist intelligence. The results of this study are that students with verbal linguistic intelligence fulfill all indicators on the components of the literacy thinking process and can write answers in easily understood languages. Students with mathematical logical intelligence fulfill all indicators on the components of the literacy thinking process but there are stepping steps in writing answers. Whereas students with naturalist intelligence do not fulfill one of the indicators on the components of the first literacy process, namely students do not write mathematical situations using symbols. Students with verbal linguistic intelligence, students with mathematical logical intelligence and students with naturalist intelligence have different strategies in solving problems. Students with verbal linguistic intelligence tend to use detailed translation, students with mathematical logical intelligence are able to use mathematical operations well and students with naturalist intelligence tend to use images to solve problems. Keywords: Thinking in mathematical literacy, multiple intelligence, questionnaire